The Effect of Antithrombin III-Independent Thrombin Inhibitors and Heparin on Fibrin Accretion onto Fibrin-Coated Polyethylene - Rubens, F D; Weitz, J I; Brash, J L; Kinlough-Rathbone, R L (Thrombosis and Haemostasis, 1993)
Prosthetic vascular grafts become coated with a layer of fibrin that contributes to graft thrombosis and occlusion. We compared the effect of antithrombin III-independent inhibitors of thrombin with heparin for their ability to prevent fibrin accretion onto a model of a vascular graft formed in vitro by coating polyethylene tubing with thrombin bound to a layer of polymerized fibrin. Equivalent antithrombin concentrations of heparin, D-Phe-Pro-Arg CH2Cl (PPACK), recombinant hirudin (r-hirudin), and Hirulog-1 were added to barium chloride-adsorbed plasma containing radiolabelled fibrinogen. Whereas, PPACK and r-hirudin persistently inhibited fibrin accretion, the inhibition by heparin was transient. Hirulog-1 had no effect on early fibrin accretion and was actually associated with enhanced accretion at 30 min (control 11.7 ± 2.0 μg fibrin/cm2; Hirulog-1, 18.4 ± 3.5 μg fibrin/cm2, p <0.001). Both Hirulog-1 and r-hirudin displaced radiolabelled thrombin from the fibrin surface. Whereas hirudin-thrombin complexes are stable, Hirulog-1 produces only transient inhibition of the displaced thrombin thereby accounting for the enhanced fibrin accretion with this anticoagulant. These studies show that the antithrombin III-independent inhibitors, r-hirudin and PPACK, are more effective inhibitors of fibrin accretion onto fibrin-coated polyethylene than heparin or Hirulog-1. In addition, they emphasize the importance of determining the ability of anticoagulants to displace thrombin from fibrin and to form stable thrombin-inhibitor complexes; lack of stability of thrombin-inhibitor complexes must be countered by levels of anticoagulant that are adequate to maintain its effectiveness.